A review of the use of computational technology in applied behavior analysis. (June 2019) - Trevisan, Diogo Fernando; Becerra, Lorraine; Benitez, Priscila; Higbee, Thomas S; Gois, João Paulo
Applied behavior analysis (ABA) is a behavioral science that aims to teach specific and socially relevant behaviors to people with different repertoires. Technology can aid behavior analysis interventions supporting different educational agents (e.g. psychologists, parents, and teachers) as well as patients. In this article, we reviewed how researchers are using technology in ABA interventions with children with autism spectrum disorder (ASD). We present the results obtained from a systematic review of the literature. The purpose was to map the employment of the computational technology in ABA interventions, as well as to discuss the primary technologies used, their benefits, and their limitations. Based on our review, we noticed that technology-based interventions are in the early stages of development. We evidenced it by the methodological limitations in many of the studies we found, and the relatively simplistic nature of many of the technological applications (e.g. inability to customize the software to meet individual learner needs). We also provide suggestions, based on these findings, for how researchers may advance the studies in this area to improve the lives of children with ASD and their families.